The Interplay Between the Early Work and Family Trajectories of Young Adult Women Born in West Germany: Differences by Parental Origins - Cristina Samper Mejia (Journal of International Migration and Integration, 2021)
Using data from the German Socio-Economic Panel (GSOEP), this paper employs sequence analysis to identify "typical" early (observation window limited to ages 15 to 30) employment and family formation trajectories among female second-generation migrants in Germany. For the employment domain of the life course, four types of employment trajectories were identified according to their modal states: "long education," "full-time employment," "part-time employment," and "non-employment." For the family domain of the life course, three types of family trajectories were identified: "postponement of family formation," "early family formation," and "early single motherhood." For the analysis on cluster affiliation, a multinomial logistic regression was used to investigate how parental origin relates to jointly determined employment and family trajectories. As expected, the descriptive results showed that trajectories of low labor market participation are highly related to trajectories of early family formation. The categorization by parental origins shows that there were few differences in the trajectories of most native and G2 women groups. One pattern that stood out was that compared to other origin groups, G2 women of Turkish parental origin were more likely to be on an early family formation path, and they were more likely to be on a path with multiple non-employment spells. In the modeling strategy, the remaining differences in the women's patterns were partially explained by the differences in their socioeconomic backgrounds (compulsory school track and the father's professional degree) and their maternal employment role models (the mother's employment when the woman was age 15).
Keywords: 300; Second-generation women; Sequence analysis; Employment trajectories; Family formation trajectories; West Germany